Microanalysis Study on Hydrothermal Synthesis of Mg, Al-Hydrotalcite - Qiu1, Man-De; Li1, Xu; Dai1, Ai-Mei; Yang1, Pan; Wang1, Xiao-Yan; Bai1, Guo-Yi (Asian Journal of Chemistry, 2014)
In this study, the reactants are Al(NO3)3, Mg(NO3)2, Na2CO3 and precipitant is NaOH. The Mg, Al-hydrotalcite (Mg-Al-LDH) crystals is prepared by hydrothermal method. The products are investigated by X-ray diffraction, scanning electron microscope and X-ray energy dispersive spectrometer. The influences of Mg-Al-LDH crystals micro-structure and growth are systematic researched in different conditions of pH values, hydrothermal temperature and reaction time. At the same time, we discussed the growth mechanism. The results indicated that the systematic pH value has great influence on growth of Mg-Al-LDH. The growth units [Mg-(OH)6]4- and [Al-(OH)6-]3- can not form when the pH value is lower, so the product is not Mg-Al-LDH. While when pH=12, the formation of the ligand tend to stabilize and the hexagon Mg-Al-LDH has good crystalline and regularity. Keeping pH value at 12 and increasing the temperature, the crystals size tends to increase. When the temperature reached 160 °C, the product size is stable and is about 230-300 nm. When the system is in the optimum conditions of pH value and temperature, the reaction time has hardly any influence on crystals growth. As long as hydrothermal system is balanced for a certain time, the good crystalline Mg-Al-LDH crystals can be prepared but increasing time is only in favor of the crystals growth and regularity. The energy dispersive spectrometer analysis result verified that the Mg/Al is about 3 which approached to the theoretical value.